Psychological Burnout among Kindergarten and First Three Grades Teachers at Rania Governorate in Saudi Arabia - Al-Sharari, Hadwa Mohmmad Salam (Journal of Educational and Psychological Sciences, 2025)
The purpose of the study is to investigate the degree of burnout among kindergarten teachers first three grades teachers in Rania Governorate in Saudi Arabia. The study adopted descriptive analytical approach, within a burnout scale consisting of (30) items, responded by a sample of (167) teachers. The findings showed that the level of burnout among teachers was average. There were significant statistical differences attributed to the effect of the academic stage, in favor of the first three grades. There were significant statistical differences attributed to the effect of years of experience, and the differences were in favor of less than 5 years. In light of the results, a set of recommendations were presented.